The Geology of Placer Deposits - W. E. Cockfield (Canadian Institute of Mining, Metallurgy and Petroleum, 1932)
This paper is not intended as an original contribution to this subject, but rather as a review of the main theories which are held with regard to placer deposits, with, of course, particular reference to the placers of British Columbia. The present interest in gold mining has, however, brought the subject of placers to the fore, and possibly a brief outline of the geology of such deposits will serve as a basis for discussion on the subject. In Canada, the most valuable of our placers are deposits of gold, and consequently the discussion will centre largely on placer-gold deposits. The same principles apply, of course, to placer deposits of other metals. The Origin of Placer Deposits As a starting point, the idea which is prevailingly held is that placer or alluvial gold is detrital in origin, that is to say, the gold originally existed in veins, lodes, or disseminations in the country rock of the regions in which the placer deposits are now found, and that, through the various erosive forces of nature, it was liberated from those veins or lodes and concentrated in the form in which we now find it. 1 have not time to go thoroughly into the proof of this, but the lines of evidence are many. If we take the Cariboo district as a typical example, Johnston and Uglow(l) have shown, first of all, that the placer and vein gold are identical in character. Crystals occur both in the placers and in the lodes, but the crystals in the placers are nearly always slightly worn, indicating transportation.